Associations between Depression and Anxiety with Sleep Quality in Post Stroke Patients - Surbakti, Utama Hadiputra; R.A. Dwi Pujiastuti; Kiking Ritarwan (CoinReads Media Prima, 2023)
Introduction: Sleep disorders are common in stroke patients and can affect 20% - 78% of patients. Stroke patients also often experience depression and anxiety associated with a decrease in the patient's sleep quality. The purpose of this study was to determine the relationship between depression and anxiety with sleep quality in post-stroke patients. Method: This study used a cross-sectional design. The research subjects were post-stroke patients at the neuro polyclinic at H. Adam Malik General Hospital Medan and Satellite Hospital during July - December 2022 who met the inclusion criteria. Assessment of depression, anxiety and sleep quality used Hamilton Depression Rating Scale (HDRS), Hamilton Anxiety Rating Scale (HARS), and Pittsburgh Sleep Quality Index (PSQI) Questionnaires, respectively. Data were analyzed using Spearman's correlation test. Results: Bivariate analysis found that there was a strong relationship between the HDRS score and the PSQI score (r = 0.708; p <0.001), and the HARS score and PSQI (r = 0.650; p <0.001). Conclusion: There was strong correlation between depression and anxiety with sleep quality in post-stroke patients.